International accreditation for acute stroke care: lessons learnt from a Kenyan Stroke Centre - Sokhi, Dilraj Singh (Frontiers in Stroke, 2025)
BackgroundThe prevalence of stroke is increasing in Africa, yet resources remain limited in managing the disease. Whilst there are international guidelines on how to set up and manage stroke services, even in resource-limited settings, the uptake remains low. We describe here the opportunities and challenges we faced whilst setting up a stroke care pathway of international standards in a regional referral hospital in East Africa.MethodsWe describe how we adapted international stroke care guidelines for acute primary stroke (including both ischemic and hemorrhagic stroke), and used these to inform our stroke care pathway. We highlight opportunities of leveraging on multi-disciplinary involvement, as well as challenges of implementing the pathway.ResultsOur hospital was accredited by the Joint Commission International with a Clinical Care Programme Certification in May 2021. However, there were strategic improvement plans recommended that needed to be addressed for future re-accreditations, including having a dedicated stroke unit and addressing shortfalls in thrombolysis and thrombectomy timelines. We discuss the challenges faced with these and other relevant findings from the accreditation process.ConclusionInternational accreditation of our hospital provides an example of how to adapt international guidelines to local contexts. The description of our experience may be useful for other healthcare institutions from resource-limited settings who strive to improve the quality of stroke care they provide.